Numerical Simulation Study and Analysis of Water Inrush from Floor Concealed Subsidence Column during Mining. Issue 1 (1st June 2022) - Wei, Fu
Abstract: In order to clarify the role of mining on the surrounding rock failure and water inrush of the karst collapse column in the working face floor, the concealed karst collapse column in the floor of Geting Coal Mine is taken as the research object, and the FLAC3D numerical simulation software is used to analyze the mining process. The stress field in the vertical direction, the plastic failure zone and the displacement change in the vertical direction are analyzed and studied, and the water inrush process of the hidden floor karst collapse column under different advancing distances is analyzed. The research results show that with the continuous increase of the advancing distance, the plastic failure range of the karst collapse column continues to increase, and the vertical displacement of the floor continues to increase. When the plastic failure zone of the coal floor and the plastic failure zone of the karst collapse column are connected, Water inrush accidents from the karst collapse column of the floor are prone to occur.